Key to species of the genus Xenovarta Viraktamath (Hemiptera: Cicadellidae: Deltocephalinae) with description of a new species from China - Xing, Jichun (Zootaxa, 2018)
A new leafhopper species, Xenovarta lii sp. nov., is described and illustrated from Yunnan Province, China, and a key is given to separate species of this genus. A map showing the geographic distribution of the new species is also provided. The type specimen of the new species is deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).